2022
DOI: 10.1111/hiv.13304
|View full text |Cite
|
Sign up to set email alerts
|

Use of antiretroviral therapy in pregnancy and association with birth outcome among women living with HIV in Denmark: A nationwide, population‐based cohort study

Abstract: Objective To describe antiretroviral therapy (ART) regimens during pregnancy among women living with HIV (WLWH) in Denmark and to examine the association between ART use in pregnancy and adverse birth outcomes. Methods A population‐based cohort study including all pregnancies among WLWH in Denmark between 2000 and 2019. Data were collected through national registries. Temporal trends of ART use in pregnancy were evaluated. Logistic regression models were used to examine the association of ART use in pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
3
6
1
Order By: Relevance
“…Therefore, the use of ART before pregnanc y has rapidly increased since most women living with HIV are of childbearing potential ( 1 ). Consistent with the results of other studies in Europe ( 6 , 23 ), we observed that LPV/r-based regimens and NNRTI, especially EFV-based regimens, were the commonly used ART regimen among PWLHIV. The proportion of LPV/r use has been increasing in recent years, per our study findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the use of ART before pregnanc y has rapidly increased since most women living with HIV are of childbearing potential ( 1 ). Consistent with the results of other studies in Europe ( 6 , 23 ), we observed that LPV/r-based regimens and NNRTI, especially EFV-based regimens, were the commonly used ART regimen among PWLHIV. The proportion of LPV/r use has been increasing in recent years, per our study findings.…”
Section: Discussionsupporting
confidence: 91%
“…However, further multivariate analysis revealed no significant increased risk of PTB associated with LPV/r-NRTIs initiated before and during pregnancy. PI, especially LPV/r based regimens, have been reported to be associated with an increased risk of PTB in comparison to AZT monotherapy ( 8 , 24 ) or NNRTIs based regimens ( 7 ) or non-PI based regimens ( 33 ), although the related data still remains controversial ( 6 , 34 36 ). A multi-center observational study across eight European countries found an increased risk of PTB among PWLHIV with LPV/r-based regimens initiation before pregnancy but no increased risk of PTB associated with LPV/r-based regimens initiated during pregnancy ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vertical transmission of HIV occurred in one delivery (0.86%). This is similar to the national finding of a 0.27% transmission rate between 2012 and 2014 ( 8 ), as well as rates reported from both the UK and other high-income countries over the last 10 years ( 26 , 28 , 30 , 31 , 33 , 35 , 41 , 42 ). The preterm delivery rate of 11.2% is lower than the national rate of 12.5% amongst WLHIV, but remains considerably higher than the national rate of 7.8% amongst all women ( 14 , 43 ).…”
Section: Discussionsupporting
confidence: 89%
“…The rate of low birth weight was 16%. This is comparable to national UK data ( 44 ), whilst other similar cohorts in high-income countries report rates ranging from 12 to 25% ( 28 , 41 , 42 , 45 , 46 ). Fifteen percent of infants were SGA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation